Postpartum Depression and Breastfeeding Success among Postpartum Mothers: A Systematic Review - Maharani (Asian Journal of Health Research, 2026)
Introduction: Postpartum depression is a frequent maternal mental health concern that can disrupt confidence, responsiveness, and daily care during the early postpartum period. Breastfeeding success is not limited to exclusive breastfeeding, but also includes early initiation, continuation, maternal satisfaction, and breastfeeding self-efficacy. This systematic literature review synthesized recent evidence on the relationship between postpartum depression and breastfeeding success among postpartum mothers.    Methods: A PRISMA-guided review was conducted using Scopus as the target database. The search combined terms for postpartum depression, postnatal depression, maternal depression, breastfeeding, exclusive breastfeeding, lactation, breastfeeding self-efficacy, mother, maternal, and postpartum. English language open-access articles published from 2020 to 2026 were screened. Forty-five studies met the eligibility criteria and were synthesized narratively.     Results: The evidence consistently indicated that postpartum depressive symptoms were associated with lower exclusive breastfeeding, early cessation, reduced breastfeeding self-efficacy, and more negative breastfeeding experiences. Longitudinal, cross-sectional, review, and intervention studies also showed that social support, maternal stress, breastfeeding pressure, prenatal planning, and midwife-led support shaped this association.    Conclusion: Postpartum depression and breastfeeding success should be addressed as integrated maternal outcomes. Midwifery practice needs routine psychological screening, lactation counseling, partner involvement, and non-judgmental support for mothers who breastfeed, combine feeding, or discontinue breastfeeding.